2018
DOI: 10.1128/jvi.01251-17
|View full text |Cite
|
Sign up to set email alerts
|

Genotype 2 Strains of Porcine Reproductive and Respiratory Syndrome Virus Dysregulate Alveolar Macrophage Cytokine Production via the Unfolded Protein Response

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) infects alveolar macrophages (AMΦ) causing dysregulated interferon (IFN)-α and tumor necrosis factor (TNF)-α production through a mechanism(s) yet to be resolved. Here, we show that AMΦ infected with PRRSV secreted a reduced quantity of IFN-α following the cell exposure to synthetic dsRNA. This reduction did not correlate with reduced IFNA1 gene transcription. Rather, it coincided with two events that occurred late during infection and were indicative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 82 publications
1
26
0
Order By: Relevance
“…For PRRSV, two branches of UPR pathways, IRE1-XBP1 and PERK-eIF2α, are activated. The UPR induction by PRRSV contributes to apoptosis (Huo et al, 2013;Yuan et al, 2016) and deregulates cytokine production in J o u r n a l P r e -p r o o f PAMs (Chen et al, 2017b). Further studies reveal that GP2a targets GRP78 for degradation .…”
Section: Other Cellular Pathways Involved In Prrsv Proliferationmentioning
confidence: 95%
See 1 more Smart Citation
“…For PRRSV, two branches of UPR pathways, IRE1-XBP1 and PERK-eIF2α, are activated. The UPR induction by PRRSV contributes to apoptosis (Huo et al, 2013;Yuan et al, 2016) and deregulates cytokine production in J o u r n a l P r e -p r o o f PAMs (Chen et al, 2017b). Further studies reveal that GP2a targets GRP78 for degradation .…”
Section: Other Cellular Pathways Involved In Prrsv Proliferationmentioning
confidence: 95%
“…Moreover, the UPR does not inhibit but instead stimulates efficient replication of PRRSV . In response to PRRSV infection, induction of UPR has been found not only contributing to PRRSV-induced apoptosis in host cells (Huo et al, 2013), but also involving in the regulation of viral replication and dysregulation of cytokine production in PAMs (Chen et al, 2017b).…”
Section: Other Cellular Pathways Involved In Prrsv Proliferationmentioning
confidence: 99%
“…PRRSV induces both eIF2␣ phosphorylation-dependent and -independent host translation shutoff. Previous studies have indicated that PRRSV increases the phosphorylation of eIF2␣ (23,24). It is well known that the phosphorylation of eIF2␣ causes translation to stall (40).…”
Section: Prrsv Infection Induces Translation Suppression In Cellsmentioning
confidence: 99%
“…PRRSV infection modulates normal cellular processes such as autophagy (16,17), apoptosis (18,19), and host innate immune responses (20)(21)(22). It is well known that PRRSV induces the phosphorylation of eIF2␣ and the appearance of stress granules (23,24). PRRSV GP4 and GP5 alter the gene expression profiles of stably transfected host cell lines (25).…”
mentioning
confidence: 99%
“…This cell line has previously been shown to support replication of Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) to high levels and it was demonstrated that efficacy of vaccine strains produced in this cell line was maintained at a high level following passage [2,3]. The ZMAC-4 cell line was used to investigate modulation of host stress responses to PRRSV infection [4]. In this report we describe experiments which demonstrate that ASFV isolates replicate in the ZMAC-4 cell line to levels similar to primary porcine macrophages without an adaptation step to the cell line.…”
Section: Introductionmentioning
confidence: 99%